THE DIFFERENCES BETWEEN THEORETICAL FRAMEWORK AND CONCEPTUAL FRAMEWORK IN SCIENTIFIC RESEARCH - Magvira Ardhia Pratiwi (Ide dan Dialog Desain Indonesia (Idealog), 2022)
A research it is necessary to have a theoretical and conceptual framework to guide the research path and are the basis for several stages and processes establishing research credibility. In terms, these two types of frameworks are quite similar, but in fact these two frameworks dif er from each other in their concepts and roles in research. Many researchers find it dif icult and confusing to tell the dif erence. So this article examines and provides an understanding of these two types of frameworks. This research was conducted qualitatively with a literature study to find definitions as well as similarities and dif erences. The result is to provide an understanding of the similarities, dif erences, and stages of forming a theoretical and conceptual framework in social science research. Theoretical framework is a series of models that describe observed phenomena that aim to determine relationships between variables, help researchers find research questions, find solutions to research problems, and can even be a guide for research. The conceptual framework is a series of ideas developed and ef orts to simplify the abstraction of the researcher's mind regarding the observed phenomenon so that research can be directed, well described, and easy to understand. Keywords: Theoritical, conceptual, framework, scientific research